Treatment of anthracycline extravasation from centrally inserted venous catheters - Seppo W. Langer (Frontiers Media S.A., 2011)
The treatment of accidental extravasation of anthracycline-based chemotherapy has markedly improved with the recent introduction of a systemic antidote, Savene. However, efficacy data on this treatment is mainly based on extravasation from peripheral catheters. This review presents data on 7 cases of Savene treatment of anthracycline extravasations from central venous catheters.